2005
DOI: 10.1097/01.ijg.0000176937.93143.bf
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Frequency Doubling Technology and Heidelberg Retina Tomograph

Abstract: In the entire group, cup shape measure showed to be the most significant factor correlating functional and morphologic changes. The presence of significant correlations between some HRT parameters and visual field indices in the ocular hypertensive and glaucoma subgroup suggested that HRT parameters and FDT indices could detect glaucoma damage differently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…In the past HRT and FDT perimetry have been compared with each other [30][31][32][33] and with other newly developed devices, which claim to detect glaucomatous damage at an early stage of the disease. In these comparisons, HRT and FDT perimetry competed with modern perimetric techniques 10,16,34,35 as well as with methods to inspect the nerve fiber layer.…”
Section: Discussionmentioning
confidence: 99%
“…In the past HRT and FDT perimetry have been compared with each other [30][31][32][33] and with other newly developed devices, which claim to detect glaucomatous damage at an early stage of the disease. In these comparisons, HRT and FDT perimetry competed with modern perimetric techniques 10,16,34,35 as well as with methods to inspect the nerve fiber layer.…”
Section: Discussionmentioning
confidence: 99%
“…The American Academy of Ophthalmology recently underlined how no OCT (actually the main device used to analyze structure) on US market has got a stand-alone indication for diagnosis of glaucoma [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medeiros et al showed that functional abnormalities detected by FDT perimetry were predictive of the future onset and location of standard threshold perimetry loss among glaucoma suspect subjects (34). In a recent study, Iester et al showed some correlation between HRT and FDT, in particular in the glaucoma subgroup rather than in ocular hypertension subgroup (12). In this study, significant sector and global correlations were found between HRT and FDT in patients with glaucoma, but when sector parameters were used, RA had the strongest correlation with both perimetric techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, CSM is the parameter which is almost always present in all the discriminant analysis formulas and RA is the parameter used by the Moorfields Regression Analysis (7,10,11). The aim of this study was to evaluate which HRT parameter, CSM or RA, which have been shown to have the best correlation with FDT indices among all the HRT parameters (12), was the best predictor of FDT sensitivity by using a sector-based analysis.…”
mentioning
confidence: 99%